Árvores do futuro: um guia para implementação e condução de uma oficina de orientação profissional - Souza, Angelica Ribeiro de (Brasil, 2024)
This educational product was created based on studies carried out in the dissertation “Career Guidance for Primary School Students”. The Career Guidance Guide entitled “Trees of the Future: A Guide to Implementing and Conducting a Career Guidance Workshop” was developed in e-book format in order to be a localized material accessible to the entire school and academic community so that the importance of discussing career guidance with this group of students, 9th graders, can be disseminated. This guide follows existing norms for its composition and better applicability in theoretical bases focused on the techniques presented here. The aim of this material is to contribute to the maturing of the professional inclinations of students graduating from elementary school who are interested in Integrated Secondary Education, given that the research carried out shows that career guidance aims to promote assertive and conscious choices not only in the professional field, but throughout the participant’s life project.